2022
DOI: 10.1177/11786388221105732
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Associated Factors Among Lactating Women in Sierra Leone: An Analysis of the Sierra Leone Demographic and Health Survey 2019

Abstract: Background: Anemia is a condition in which hemoglobin (Hb) concentration and/or red blood cell (RBC) numbers are lower than normal and insufficient to meet an individual’s physiological needs. The prevalence of anemia among women of reproductive age is high in Sub-Saharan Africa (SSA), including Sierra Leone. However, data on anemia among lactating women in Sierra Leone are scarce. Therefore, this study was conducted to estimate the prevalence of anemia and determine its associated factors among lactating wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Liberia and Nigeria reported severe public health threat of anaemia prevalence (42% and 55% respectively) (WHO, GHO [41]). Previous studies conducted in Sierra Leone reported anaemia prevalence of 42.2% (Statiatics Sierra Leone [13]) and 44.8% (Wirth, et al [12]) and the public health significance of anaemia was severe in both studies. Anaemia in both studies was largely mild while severe anaemia was uncommon (0.5% and 1.1% respectively).…”
Section: Review Of Previous Findings From Studies On Cbc Anaemia and ...mentioning
confidence: 60%
“…Liberia and Nigeria reported severe public health threat of anaemia prevalence (42% and 55% respectively) (WHO, GHO [41]). Previous studies conducted in Sierra Leone reported anaemia prevalence of 42.2% (Statiatics Sierra Leone [13]) and 44.8% (Wirth, et al [12]) and the public health significance of anaemia was severe in both studies. Anaemia in both studies was largely mild while severe anaemia was uncommon (0.5% and 1.1% respectively).…”
Section: Review Of Previous Findings From Studies On Cbc Anaemia and ...mentioning
confidence: 60%
“…Factors like age, education, reproductive and obstetric factors, and maternal health service usage and residency have been found to be associated with anemia in WRA (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 98%
“…Developmental delays in young children are the result of nutritional problems that arise from an early age. A nutrition journal shows that a history of anemia during pregnancy is a risk factor for stunting, plus genetic triggers from parents who have a history of anemia (Arinda et al, 2022).…”
Section: Introductionmentioning
confidence: 99%